THE FUNCTION OF STYLISTIC RE-REGISTRATION IN THE LINGUISTIC-STYLISTIC ANALYSIS OF THE NOVEL PAPER DRAGONS BY MIRA OTASEVIC (Heritage, 2023)
The subject of this paper is a linguistic stylistic analysis of the functional value of stylistic re-registration in the novel Paper Dragons by Mira Otasevic (2008). The aim of the research is to indicate the influence of stylistic re-registration in the creation of a hybrid genre form, in which a documentary-fictional novel is formed through the technique of literary collage. The effects and consequences of re-registration in the work are examined through the adaptation of non-literary functional styles, sub-styles, and genres to the aesthetic function of the literary-artistic text, as well as through the influence of intertextuality. By applying the criteria of integral stylistics, the paper sheds light on the functional value of the polyvalent structure of the novel, where the hybridization of literary language has a stylistic value of reviving and maintaining the culture of memory.
Keywords: Mira Otasevic, Paper dragons, Serbian literature, linguistic-stylistic analysis, integral stylistics, stylistic re-registration.